Wild at Heart: How Informal Learning Experiences Occur at the Local Wild Food Challenge - Kajzer Mitchell, Ingrid; Low, Will (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2026)
This case study explores the adult learning experience of participants at a food festival, the Local Wild Food Challenge (LWFC). Food festivals, where participants engage in multisensory experiences within a “foodscape,” have the potential to facilitate different informal adult learning processes. Whether incidental or intentional, the learning experienced at the LWFC also fits instrumental and communicative learning paradigms, which are precursors to transformative learning. Learning about and reflecting on new ways to gather, harvest, and prepare wild foods can in turn build the foundation for critical self-reflection around food self-sufficiency, as well as a subtle shift in frames of reference regarding wild foodscapes that lie beyond mainstream corporate food systems. Thus, the study positions the food festival as an important site for informal adult learning, potentially opening participants up to learning about alternative sustainable ways of living.